Morphofunctional evolution of the pelvic girdle and hindlimbs of Theropoda (Dinosauria, Saurischia) with emphasis on the Megalosauroidea lineage - Mauro Bruno da Silva Lacerda (2023)
The Theropoda clade can be considered one of the most successful dinosaur groups, both throughout the Mesozoic Era and nowadays due to the wide diversity and variety of forms of the extant representatives of the group. One of the basic features of dinosauromorphs and the Theropoda clade is the bipedalism: a widespread locomotor adaptation that, unlike quadrupedalism, probably had a unique evolutionary origin. Among the extinct lineages, several clades are recognized as non-avian theropods; among these, the Megalosauroidea lineage stands out, which includes the oldest dinosaur ever described in the literature – Megalosaurus bucklandii, in addition to aberrant and large-sized species such as Spinosaurus aegyptiacus. The main diagnostic features of the group include: (1) presence of a prominent deltopectoral ridge on the humerus, (2) extended anterior maxillary ramus, (3) presence of separate interdental plates, among other features considered to be synapomorphic. In this thesis, I analysed the macroevolution and disparity of the morphological characters of the locomotor apparatus – pelvic girdle, stylopodium and zeugopodium – in theropod dinosaurs, with emphasis on the clade Megalosauroidea. Additionally, the musculature of part of the locomotor apparatus of the early-diverging megalosauroids Piatnitzkysaurus floresi and Condorraptor currumilli was reconstructed.